Co-Creating Sustainable Tourism through Stakeholder Collaboration: Insights from Mandalika, Indonesia - Adi Purmanto; Yuniati Yuniati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Sustainable tourism development requires effective collaboration among multiple stakeholders to ensure balanced economic growth, environmental conservation, and community well-being. Despite increasing attention to stakeholder collaboration in tourism studies, limited research has explained how collaborative governance facilitates value co-creation in emerging tourism destinations. This study aims to explore how stakeholder collaboration contributes to sustainable tourism development through collaborative governance in Mandalika, Indonesia. A qualitative case study approach was employed using semi-structured interviews, field observations, and document analysis. The data were analyzed through thematic analysis to identify key patterns of stakeholder interaction and governance processes. The findings reveal that stakeholder collaboration is strengthened through institutional coordination, trust-building, and participatory decision-making, which collectively enable value co-creation in the form of tourism innovation, community empowerment, cultural preservation, enhanced tourist experiences, and local economic development. Nevertheless, challenges remain, including unequal community participation, disparities in economic benefit distribution, and differences in institutional capacity. This study proposes an Integrated Sustainable Tourism Collaboration Model that demonstrates the dynamic relationship between stakeholder collaboration, collaborative governance, value co-creation, and sustainable tourism development. The proposed model extends the understanding of sustainable destination governance while providing practical insights for policymakers and destination managers seeking to strengthen collaborative tourism development in emerging destinations.